Modeling sustainable long-term electricity supply-demand in Africa - Nadia S. Ouedraogo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper develops a scenario-based model to identify and provide an array of electricity demand in Africa, and to derive them from the African power system of development. A system-based approach is performed by applying the scenario methodology developed by Schwartz in the context of the energy-economic modeling platform 'Long-range Energy Alternative Planning'. Four scenarios are investigated. The Business as Usual scenario replicates the regional and national master plans. The renewable promotion scenario increases the share of renewable energy in the electricity mix. The demand- and supply-side efficiency scenarios investigate the impact of energy efficiency measures on the power system. The results show an increase in electricity demand by 4 per cent by 2040, supply shortages, and high emissions of greenhouse gases. Contrary to expectations, the renewable energy scenario did not emerge as the best solution to a sustainable electrification of the region. The energy efficiency scenarios have allowed us to draw a sustainable pathway for electrification.
Keywords: 330; energy planning model simulation; electricity; sustainable development; climate change; Africa